Degradation of Conazole Fungicides in Water by Electrochemical Oxidation - Urzua-Moll, A; Ureta-Zanartu, M; Sepulveda-Palma, F; Salazar-Gonzalez, R; Gonzalez-Vargas, C; Gonzalez-Vargas, C (2013)
The electrochemical oxidation (EO) treatment in water of three conazole fungicides, myclobutanil, triadimefon and propiconazole, has been carried out at constant current using a BDD/SS system. First, solutions of each fungicide were electrolyzed to assess the effect of the experimental parameters such as current, pH and fungicide concentration on the decay of each compound and total organic carbon abatement. Then a careful analysis of the degradation by-products was made by high performance liquid chromatography, ion chromatography and gas chromatography coupled with mass spectrometry in order to provide a detailed discussion on the original reaction pathways. Thus, during the degradation of conazole fungicides by the electrochemical oxidation process, aromatic intermediates, aliphatic carboxylic acids and Cl- were detected prior to their complete mineralization to CO2 while NO3- anions remained in the treated solution.This is an essential preliminary step towards the applicability of the EO processes for the treatment of wastewater containing conazole fungicides. © 2013 Elsevier Ltd.